Gender differences in white-collar offending and supervision - Ruhland, Ebony L. (Criminal justice studies, 2020)
This study examines gender differences in white-collar offending in a sample of men and women on federal community supervision (probation and supervised release). Compared to studies conducted in the 1970s and 1980s women’s participation in white collar crime has changed in some ways but also has striking similarities to those earlier studies. Study findings illustrate that men still comprise a larger share of those who commit white-collar offenses, but the proportion of women is growing. This study highlights other gendered differences in white-collar offending as relates to important demographic characteristics and community supervision. Some of the key differences found by gender concern educational attainment and marital status, which are similar to differences exhibited in prior research. The discussion sections outline the implications as well as compares these new findings to historical studies on gender and white-collar crime.